BALOK LAMINASI DARI KAYU KELAPA (Cocos nucifera L) - Purwanto, Djoko (Jurnal Riset Industri Hasil Hutan, 2010)
Laminated beams of two, three and four layers of coconut wood the bottom, middle and top part with PVAc adhesive (Poly Vinyl Acetat). The purpose of this research is to make coconut wood laminate beams for structural building materials. The results showed that the laminated beam two, three and four layers are made of wood bottom and middle part produce strong mechanical strength class II and III, so that qualified for structural building materials (SNI.03-3527-94). laminated beams of two, three and four are made of wood mechanical strength of the top part produces a strong class IV and meet for structural building materials (SNI.03-3527-94). Keywords: laminated beams, coconut wood